Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Badan Pengawas Pemilihan Umum (Bawaslu) Kota Tangerang - Maharani Maharani; Oki Iqbal Khair (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The purpose of this study was to determine the effect of motivation and physical work environment on the performance of Tangerang City Election Supervisory Agency (Bawaslu) employees. The method used was quantitative. The sampling technique used saturated sampling and obtained a sample of 50 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The population in this study were Tangerang City Election Supervisory Agency (Bawaslu) employees and the number of saturated samples was 50 respondents. Data collection methods were through questionnaires with a Likert scale, observation, and literature studies. The results of this study were that motivation had a significant effect on employee performance with a determination coefficient value of 46.5% and the hypothesis test obtained t count > t table or (6.459 > 2.010). Physical Work Environment had a significant effect on employee performance with a determination coefficient value of 80% and the hypothesis test obtained t count > t table or (2.042 > 2.010). Motivation and the physical work environment simultaneously significantly influence employee performance, with the regression equation Y = 16,862 + 693X1 + 0.89X2, with a coefficient of determination of 47.3%, while the remaining 52.7% is influenced by other factors. The hypothesis test yielded a calculated F value > F table value of 21.058 > 3.20. Keywords: Motivation; Work Environment; Performance